Cement substitution by organoclay – The role of organoclay type. (September 2015) - Kalpokaitė-Dičkuvienė, Regina; Lukošiūtė, Irena; Čėsnienė, Jūratė; Brinkienė, Kristina; Baltušnikas, Arūnas
Abstract: In this paper three organically modified clays (OC) with different functional group of modifier and basal spacing ( d 001 ) but approximately the same alkyl chain length were considered in order to identify which parameter of OC is the most characteristic for the selection of appropriate OC for cement substitution. Compressive strength and water absorption changes in hardened cement paste due to partial cement substitution by OC at various dosages (0.5 up to 6 wt%) and at water-to-solid ratios (0.27, 0.31 and 0.36) were examined. Microstructural changes evaluated by nitrogen sorption indicated that pore size distribution and especially micro and mesopores representing C–S–H structure have been much more affected by the type of modifier than the d 001 of OC. Results showed that application of OC of the same d 001, but having different functional group of modifier may result in either significant increment or reduction of the strength.